High open-circuit voltage small-molecule p-DTS(FBTTh2)2:ICBA bulk heterojunction solar cells – morphology, excited-state dynamics, and photovoltaic performance. Issue 4 (2nd December 2014) - Ko Kyaw, Aung Ko; Gehrig, Dominik; Zhang, Jie; Huang, Ye; Bazan, Guillermo C.; Laquai, Frédéric; Nguyen, Thuc-Quyen
Abstract : A high V OC of 1V is achieved in the bulk heterojunction solar cell using the solution-processed small molecule donor p-DTS(FBTTh2 )2 and indene-C60 bis-adduct acceptor. Abstract : The photovoltaic performance of bulk heterojunction solar cells using the solution-processable small molecule donor 7, 7′-(4, 4-bis(2-ethylhexyl)-4 H -silolo[3, 2- b :4, 5- b ′]dithiophene-2, 6-diyl)bis(6-fluoro-4-(5′-hexyl-[2, 2′-bithiophene]-5-yl)benzo[ c ][1, 2, 5]thiadiazole) (p-DTS(FBTTh2 )2 in combination with indene-C60 bis-adduct (ICBA) as an acceptor is systematically optimized by altering the processing conditions. A high open-circuit voltage of 1 V, more than 0.2 V higher than that of a p-DTS(FBTTh2 )2 :PC70 BM blend, is achieved. However, the power conversion efficiency remains around 5% and thus is lower than ∼8% previously reported for p-DTS(FBTTh2 )2 :PC70 BM. Transient absorption (TA) pump–probe spectroscopy over a wide spectral (Vis-NIR) and dynamic (fs to μs) range in combination with multivariate curve resolution analysis of the TA data reveals that generation of free charges is more efficient in the blend with PC70 BM as an acceptor. In contrast, blends with ICBA create more coulombically bound interfacial charge transfer (CT) states, which recombine on the sub-nanosecond timescale by geminate recombination. Furthermore, the ns to μs charge carrier dynamics in p-DTS(FBTTh2 )2 :ICBA blends are only weakly intensity dependent implying a significant contribution of recombination from long-lived CT states and trapped charges, while those in p-DTS(FBTTh2 )2 :PC70 BM decay via an intensity-dependent recombination mechanism indicating that spatially separated (free) charge carriers are observed, which can be extracted as photocurrent from the device.